Nanoelectromechanics of superconducting weak links (Review Article) - Parafilo, A.V.; Krive, I.V.; Shekhter, R.I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Nanoelectromechanical effects in superconducting weak links are considered. Three different superconducting devices are studied: (i) a single-Cooper-pair transistor, (ii) a transparent SNS junction, and (iii) a single-level quantum dot coupled to superconducting electrodes. The electromechanical coupling is due to electrostatic or magnetomotive forces acting on a movable part of the device. It is demonstrated that depending on the frequency of mechanical vibrations the electromechanical coupling could either suppress or enhance the Josephson current. Nonequilibrium effects associated with cooling of the vibrational subsystem or pumping energy into it at low bias voltages are discussed.